The bidirectional association between maternal speech and child characteristics. Issue 2 (8th March 2020) - MIMEAU, Catherine; CANTIN, Édith; TREMBLAY, Richard E.; BOIVIN, Michel; DIONNE, Ginette
Abstract: Our aim was to assess whether infants influence the quantity and quality of their mothers' speech to them and, in turn, whether this maternal speech influences children's later language. As 189 mothers interacted with each of their twins at age 0;5, we calculated the number of utterances, the proportion of sensitive utterances, and the proportion of self-repeated utterances they produced. We later assessed the twins' language comprehension and production when they were 1;6, 2;6, and 5;2. Quantity of maternal speech predicted child language at 5;2, whereas sensitivity predicted child language at 2;6 and 5;2 and partial self-repetition predicted child language at 1;6. Conversely, sensitivity and partial self-repetition in maternal speech at 0;5 were associated with genetic factors from the child, indicating that infant characteristics influence the quality of maternal speech. Overall, our findings stress the importance of considering both directions in the association between maternal speech and child characteristics.